2017
DOI: 10.1287/mnsc.2016.2538
|View full text |Cite
|
Sign up to set email alerts
|

Incompatible European Partners? Cultural Predispositions and Household Financial Behavior

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 37 publications
2
53
0
3
Order By: Relevance
“…41 Table O.A.16 presents estimation results for all samples. We find that an increase in the share of neighbors with economics or business education and some college attendance among this expanded circle of neighbors results in the same pattern of statistical signifi- 39 The IHS transformation introduces some allowance for non-linearity: for example, in a linear probability model, the coefficient on this variable is very close to the semi-elasticity of the share. Moreover, in unreported regressions, we have found that using the level of the share instead of its IHS transformation produces similar implications as those discussed in the text.…”
Section: Introducing More Recent Neighboring Immigrantsmentioning
confidence: 64%
See 3 more Smart Citations
“…41 Table O.A.16 presents estimation results for all samples. We find that an increase in the share of neighbors with economics or business education and some college attendance among this expanded circle of neighbors results in the same pattern of statistical signifi- 39 The IHS transformation introduces some allowance for non-linearity: for example, in a linear probability model, the coefficient on this variable is very close to the semi-elasticity of the share. Moreover, in unreported regressions, we have found that using the level of the share instead of its IHS transformation produces similar implications as those discussed in the text.…”
Section: Introducing More Recent Neighboring Immigrantsmentioning
confidence: 64%
“…Guiso et al (2006) provided evidence that trust is influenced by ethnic origin in US data, while Guiso et al (2003) found evidence that trust is influenced by religion, both pointing to the relevance of culture. Haliassos et al (2017) found that financial behavior differs across cultural groups of migrants, controlling for a range of characteristics, but these differences diminish with exposure to host country institutions. 9 For evidence on the speed of assimilation of financial behavior of immigrants to Sweden, see Haliassos et al (2017).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The growth tilt of immigrants can be attributed to both behavioral biases and cultural effects. Calvet, Campbell, and Sodini (2007) show that immigrants bear more idiosyncratic risk in their financial portfolios, and Carroll, Rhee, and Rhee (1999), Christelis, Georgarakos, and Haliassos (2013), and Haliassos, Jansson, and Karabulut (2015) document that cultural effects impact immigrant savings rates, leverage, and equity and real estate investments. Our work shows that behavioral and cultural effects might also drive the value tilt.…”
Section: Relation To Sentiment-based Theoriesmentioning
confidence: 96%